China’s Economic Growth in 2010–2017: Analysis from the Perspective of the Input-Output Model and Modern Monetary Theory - A. A. Bykov; S. A. Tolkachev; U. A. Parkhimenka; T. V. Shablinskaya (Финансы: теория и практика, 2021)
The article aims to analyze the external and internal growth factors of the People’s Republic of China in 2010–2017. The authors use methods such as input-output modeling, statistical methods, content analysis of scientific publications. The study explores different perspectives on China’s rapid economic growth in recent decades. In particular, the authors consider neoclassical models that investigate and explain the dynamics of the Chinese economy due to the accumulation and development of factors of domestic production. Some studies are analyzed, which consider economic growth as a result of the final demand, both internal and external, on the basis of the input-output approach. The article examines the views that interpret the monetary policy as one of the most important factors in stimulating economic growth. The authors, based on the economic growth decomposition method, determine the components due to domestic demand and the components due to exports, both for the entire Chinese economy and for particular industries. Сalculations based on the data of input-output balances for 2010–2017 allowed the authors to draw a conclusion about the significant contribution of domestic demand to the economic growth of China in the context of active monetary stimulus. Thus, the novelty of the study is ensured by the fact that Thirlwall’s law does not apply to modern China –– stimulating the economy in China does not lead to a decrease in the trade surplus due to the monetary and financial sovereignty, industrial competitiveness, and the innovative economic development. The search for tools for adapting China’s monetary policy to the realities of Russia and the Republic of Belarus opens up opportunities for future research on the topic.